Evaluation of Seismic Response Trends from Long-Term Monitoring of Two Instrumented RC Buildings Including Soil-Structure Interaction. (16th May 2012) - Butt, Faheem; Omenzetter, Piotr
Abstract : This paper presents analyses of the seismic responses of two reinforced concrete buildings monitored for a period of more than two years. One of the structures was a three-storey reinforced concrete (RC) frame building with a shear core, while the other was a three-storey RC frame building without a core. Both buildings are part of the same large complex but are seismically separated from the rest of it. Statistical analysis of the relationships between maximum free field accelerations and responses at different points on the buildings was conducted and demonstrated strong correlation between those. System identification studies using recorded accelerations were undertaken and revealed that natural frequencies and damping ratios of the building structures vary during different earthquake excitations. This variation was statistically examined and relationships between identified natural frequencies and damping ratios, and the peak response acceleration at the roof level were developed. A general trend of decreasing modal frequencies and increasing damping ratios was observed with increased level of shaking and response. Moreover, the influence of soil structure interaction (SSI) on the modal characteristics was evaluated. SSI effects decreased the modal frequencies and increased some of the damping ratios.